Association of impulsivity, risk taking and neurocognitive functioning with alcohol use in preadolescents and adolescents - Rivarola Montejano, Gabriela; Pilatti, Angelina; Pautassi, Ricardo Marcos (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
Underage drinking is associated with a wide range of negative consequences, including alterations in brain development and poor cognitive functioning. Personality traits linked to drinking include impulsivity, sensation seeking and risk taking. The present study examined, separately in preadolescents (11 to 13 years old) and adolescents (14 to 16 years old), the bivariate and multivariate relationship between impulsivity, risk taking, cognitive flexibility and alcohol consumption. Preadolescents and adolescents (n = 974; M age = 13.30 ± 0.955; 54.5% women; 56.5% preadolescents) of Cordoba (Argentina) completed a survey assessing trait-like impulsivity (UPPS-P Scale) and alcohol use. They also underwent the Balloon Analogue Risk Task, the Go/No-Go Task and the Wisconsin Card Sorting Test. Trait-like impulsivity was significantly associated to substance use behaviors in preadolescents and adolescents. In the younger, but not in the older group, higher scores in risk taking and inattention explained higher frequency of alcohol use. In contrast, alcohol use in the adolescents was associated with diminished cognitive flexibility. The present study helps disentangle predictors of underage drinking at two stages of adolescence. Prevention and intervention strategies should attend the noted differences between preadolescents and adolescents.